The local callan-symanzik equation: structure and applications - Baume, Florent; Keren-Zur, Boaz; Rattazzi, Riccardo; Vitale, Lorenzo (Journal of high energy physics, 2014)
The local Callan-Symanzik equation describes the response of a quantum field theory to local scale transformations in the presence of background sources. The consistency conditions associated with this anomalous equation imply non-trivial relations among the β-function, the anomalous dimensions of composite operators and the short distance singularities of correlators. In this paper we discuss various aspects of the local CallanSymanzik equation and present new results regarding the structure of its anomaly. We then use the equation to systematically write the n-point correlators involving the trace of the energy-momentum tensor. We use the latter result to give a fully detailed proof that the UV and IR asymptotics in a neighbourhood of a 4D CFT must also correspond to CFTs. We also clarify the relation between the matrix entering the gradient flow formula for the β-function and a manifestly positive metric in coupling space associated with matrix elements of the trace of the energy momentum tensor.
Gesehen am 28.07.2020